Geotourism potential and challenges in the Archipelago of San Andrés, Providencia, and Santa Catalina (Colombia) - Manco-Jaraba, Dino Carmelo; Ríos Reyes, Carlos Alberto; Castellanos Alarcón, Óscar Mauricio (Turismo y Sociedad, 2024)
The Archipelago of San Andrés, Providencia, and Santa Catalina (Colombia) is a well-established tourist destination with numerous geosites that show a marvelous natural and cultural heritage of great importance and attractive for the development of geotourism. Although this region is visited mainly for its spectacular coastal landscape, until now, there was a lack of geological information and interpretation about those emblematic geosites. Therefore, it is very important to develop a geoconservation strategy by promoting sustainable geotourism through improving the knowledge of the geological elements of this region. The landscape value of this region must be globally recognized to improve and protect its heritage resources through geotourism and geoeducation with geoconservation purposes, so that it motivates an efficient management that describes guidelines that promote the development of an appropiate tourist infrastructure, centers of scientific and cultural interpretation, dissemination and educational materials, active exchange with geoparks, continuous improvement and participation of the local communities.
El archipiélago de San Andrés, Providencia y Santa Catalina (Colombia) es un destino turístico consolidado con numerosos geositios que muestran un maravilloso patrimonio natural y cultural de gran importancia y atractivo para el desarrollo del geoturismo. Si bien esta región es visitada principalmente por su espectacular paisaje costero, hasta ahora faltaba información e interpretación geológica sobre estos emblemáticos geositios. Por lo tanto, es muy importante desarrollar una estrategia de geoconservación que promueva el geoturismo sostenible por medio de la mejora del conocimiento de los elementos geológicos de esta región. El valor paisajístico de esta región debe ser reconocido a nivel mundial para mejorar y proteger sus recursos patrimoniales por medio del geoturismo y la geoeducación con fines de geoconservación, de manera que se motive una gestión eficiente que describa lineamientos que promuevan el desarrollo de una adecuada infraestructura turística, centros de interpretación científica y cultural, materiales de difusión y educativos, intercambio activo con geoparques, mejora continua y participación de las comunidades locales.
Keywords: coastal geomorphology; geodiversity; geotourism; geoeducation; Archipelago; WOS